Factors precipitating erythropoiesis-stimulating agent responsiveness in a European haemodialysis cohort: case-crossover study - Gillespie, Iain A.; Macdougall, Iain C.; Richards, Sharon; Jones, Vincent; Marcelli, Daniele; Froissart, Marc; Eckardt, Kai-Uwe (Pharmacoepidemiology and Drug Safety, 2015)
Hyporesponsiveness to erythropoiesis-stimulating agents (ESAs) is clinically and economically important in the treatment of anaemia in chronic kidney disease (CKD) patients. Previous studies focused on baseline predictors of ESA hyporesponsiveness, rather than factors associated with the transition to this state. Reversibility of ESA hyporesponsiveness has also not been studied previously.Case-crossover methodology was applied to a cohort of 6645 European CKD patients undergoing haemodialysis and prescribed ESAs. Ninety-day ESA exposure periods were defined, haemoglobin (Hb) response was calculated using the last 30 days of one period and the first 30 days of the next, and periods were classified based on a median ESA dose (80.8 IU/kg/week) and a 10 g/dL Hb threshold. Clinical, dialysis and laboratory data from patients' first hyporesponsive 'case' period was compared with the preceding responsive 'control' period using conditional logistic regression. A similar approach was applied to hyporesponsiveness reversal.Of the patients, 672 experienced hyporesponsiveness periods with preceding responsive periods; 711 reversed to normality from hyporesponsiveness periods. Transition to hyporesponsiveness was associated with hospitalization, vascular access changes or worsening inflammation, with these factors accounting for over two-thirds of transitions. Findings were largely insensitive to alternative ESA doses and Hb thresholds. Continued hospitalization, catheter insertion and uncontrolled secondary hyperparathyroidism were associated with a lack of regain of responsiveness.Transition to hyporesponsiveness is linked to the development of conditions such as hospitalization events, vascular access issues or episodes of systemic inflammation. However, a third of hyporesponsive episodes remain unexplained.
EVALuna2:3782